CVD growth of ZnO nanorods in situ on graphene and the study of its application as photoanode for solar cells - Madrigal-Monge, Gerardo (2017)
We report on the synthesis of a hybrid three-dimensional nanomaterial made up by a graphene platform in which vertically aligned ZnO nanorods (VAZNR) are grown in situ. The procedure used for growing the graphene by chemical vapor deposition (CVD) and transferring it onto glass resulted in a high quality film, as verified by multiple characterization methods. A continuous thin layer of VAZNR was deposited by CVD with high crystallinity and vertical alignment, determined by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The application of this hybrid nanomaterial was studied as photoanode of dye-sensitized solar cell (DSSC). A good mechanical stability of the hybrid in the corrosive I3-/I-electrolyte environment was shown. However, the initial good electrical conductivity of graphene was lost during the deposition of ZnO, according to electrical and electrochemical studies of the DSSC. The graphene film is damaged at temperatures of 570 ° C with oxygen concentration as low as 0.4% v/v. As a result, the DSSC showed no photoresponse when tested under illumination. The hybrid material still could be useful for other applications, like piezoelectric and biomedical devices, where graphene can work as a flexible and conformational sacrificial template in the fabrication process.